Productivity tools for professional medical and research - Galán-Rodas, Edén (2013)
Keep updated of new scientific evidence is very important for physicians in both clinical practice and research, the aim is to review the most commonly used tools. For example, health information sources that are as diverse and currently available through the web, the most common search resources are general search engines, specialized search engines, bibliographic databases, library resources from national and international organizations. Also, there is a need to manage references in a more efficient and agile way, so it is useful to use computerized bibliographic reference managers, and appropriate statistical analysis of information or applications programs that allow an unlimited set of procedures statistical synchronized. Also, there are many forms of network-based storage, where data are hosted on virtualized storage space. Finally, are some online training opportunities in different fields of scientific research from prestigious worldwide institutions.